2019
DOI: 10.2337/dc18-1953
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in the Achievement of Guideline Targets for HbA1c, Blood Pressure, and Cholesterol Among Patients With Type 2 Diabetes: A Nationwide Population-Based Study (ABC Study: JDDM49)

Abstract: Precise monthly achievement rates for reaching guideline targets for HbA 1c , blood pressure (BP), and lipid levels remain unknown. We evaluated achievement rates on a monthly basis in persons with type 2 diabetes mellitus (T2DM) and explored related factors. RESEARCH DESIGN AND METHODS This retrospective study initially analyzed data on 104,601 persons with T2DM throughout Japan. Patients whose HbA 1c , BP, and LDL cholesterol were measured ‡12 times during a 24-month period were included. We evaluated monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
(25 reference statements)
1
27
0
Order By: Relevance
“…Moreover, we did not have a data of social support from the network, contacts to network, and academic history, which also might be have impact on glycemic control. Third, because HbA1c values have seasonal variation [32], the seasonality of the sampling month might cause the bias of HbA1c values. Fourth, we could not adjust the effect of original variability of measured HbA1c, which vary within 0.12-0.18% standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not have a data of social support from the network, contacts to network, and academic history, which also might be have impact on glycemic control. Third, because HbA1c values have seasonal variation [32], the seasonality of the sampling month might cause the bias of HbA1c values. Fourth, we could not adjust the effect of original variability of measured HbA1c, which vary within 0.12-0.18% standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the prevalence and glycemic control rate of T2DM varied with seasons, which may lead to underestimate of T2DM prevalence and overestimate of T2MD glycemic control rate when epidemiological surveys conducted in hot season [6,9,10]. To our knowledge, previous T2DM prevalence surveys rarely considered the effects of ambient temperature [11].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies found that the incidence and glycemic control rate of T2DM varied with seasons, which may lead to underestimate of T2DM prevalence and overestimate of T2MD glycemic control rate when epidemiological surveys conducted in hot season [6,9,10]. To our knowledge, previous T2DM prevalence surveys rarely considered the effects of ambient temperature [11].…”
Section: Discussionmentioning
confidence: 93%
“…A population-based study in Csongrad, Hungary revealed the seasonal variation in the incidence of T2DM that the peak occurred on March and the trough occurred on August [9]. Several studies also revealed seasonal variation of glycemic control rate for T2DM cases that lower control rate emerged in cold winter [6,10]. These seasonal variations can be attributed to temperature variation to a certain extent.…”
Section: Introductionmentioning
confidence: 99%